Meagreness of Employees Is Symptomatic to Disease: A Case on Healthcare Industry. (September 2021) - Gupta, Namita; Pandey, Praveen Kumar; Pandey, Prashant Kumar
The main purpose of this study is to examine the existing workplace scenario in the healthcare industry. Furthermore, it analyses the causes and also uncovers the solutions to resolve the attrition problem confronted by the healthcare industry in India. The authors have explored the attrition phenomenon through a conceptual descriptive study conducted with the support of secondary data. The variables that play their noticeable role are lack of work-life balance, the absence of the feeling of achievement among the workers, substantial outstanding burden with nearly less remuneration and furthermore much repetitiveness of work. To conquer such situations, the organisation should work upon their inward strategies including the policies formed in consensus with the employees, increased employee participation in decision making and last but not the least, the organisation ought to introduce the mentoring programme with consistency, which will manufacture the trust among the lower level workers. The results of this study will be of interest to the modern HR world, HR and healthcare students, hospital administrators and to any HR consultant or agency wishing to study and resolve the herculean issue of attrition that obstructs the walls of organisational development.